2016
DOI: 10.1007/s13369-016-2094-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Process Parameters Effect on Mechanical and Machining Properties of Al6061–Cu–SiCp-Reinforced Metal Matrix Composite

Abstract: The present analysis emphasizes on optimization of pouring speed, stirring speed and pouring temperature for mechanical properties and machining properties of aluminium metal matrix composites. In Al6061 aluminium, alloy presence of Mg improves the wettability with SiCp. Precipitation hardening was also achieved; furthermore, the addition of 4 % Cu is more or less admired to duralumin that has precipitation hardening phenomenon when it is added above 560 • C. Precipitation hardening prevents dislocation at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The orthogonal experimental design helps to isolate the effect of each variable on the grey relational grade at various levels. For instance, the Ws at three different levels were calculated by taking the mean of GRG for the trials [1, 4, 7, [2, 5, 8], and [3,6,9]. The impact of other parameters at different levels was computed and listed in table 5.…”
Section: Grey Relational Coefficient (Grc) and Grey Relational Grade ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The orthogonal experimental design helps to isolate the effect of each variable on the grey relational grade at various levels. For instance, the Ws at three different levels were calculated by taking the mean of GRG for the trials [1, 4, 7, [2, 5, 8], and [3,6,9]. The impact of other parameters at different levels was computed and listed in table 5.…”
Section: Grey Relational Coefficient (Grc) and Grey Relational Grade ...mentioning
confidence: 99%
“…In recent years, automotive, marine, and aerospace industries utilize particulate reinforced aluminum matrix composite (PAMC) materials for their structural and nonstructural applications, thanks to their superior mechanical and thermo-physical properties such as higher stiffness, improved strength, lower densities, improved corrosion, abrasion and wear resistance [1,2]. Several pieces of research have been done on the preparation of PAMCs by incorporating different reinforcement particles such as SiC, Al 2 O 3 , ZrB 2 , B 4 C, TiC, ZrO 2, TiB 2, and evaluated their microstructure, mechanical and tribological properties [3,4]. Nowadays, minerals have emerged as potential reinforcement materials as they are amply available, inexpensive, and environment-friendly materials.…”
Section: Introductionmentioning
confidence: 99%
“…The study concentrated on the stirring speed of the alloy, and it was found that at a certain limit, the mechanical properties change drastically in the direction of not getting better. Besides, [8] studied evaluation emphasizes the optimization of stirring speed and pouring temperature for the properties of aluminum metal matrix composites. Several heights of pouring temperatures at a constant pouring speed of 2.5 cm/s were studied as input parameters throughout.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%